Analisis Putusan Pengadilan Agama Kandangan Nomor 51/PDT.G/2021/PA.KDG Tentang Isbat Nikah Poligami Perspektif Sema Nomor 3 Tahun 2018 dan Maqasid Syari’ah - Tari, Lela; Nasution, Iwan (Universitas Ekasakti, 2023)
The reseach aims to find out how the basis for the judge's consideration in deciding the polygamous marriage isbat determination case No. 51/Pdt.G/2021/PA.Kdg, where the decision is not in accordance with SEMA Number 3/2018 which states that